Catalytic dehydrogenative N-((triisopropylsilyl)oxy)carbonyl (Tsoc) protection of amines using iPr3SiH and CO21. Issue 66 (25th August 2015) - Tanaka, S.; Yamamura, T.; Nakane, S.; Kitamura, M.
<x xml:space="preserve">Abstract</x> Heterogeneous Pd/C efficiently catalyzes the dehydrogenative N-((triisopropylsilyl)oxy)carbonyl (Tsoc) protection of amines using iPr3SiH and CO2 without the liberation of any salts.